2018
DOI: 10.1007/s00330-018-5467-2
|View full text |Cite
|
Sign up to set email alerts
|

Dual-energy CT (DECT) lung perfusion in pulmonary hypertension: concordance rate with V/Q scintigraphy in diagnosing chronic thromboembolic pulmonary hypertension (CTEPH)

Abstract: • Chronic thromboembolic pulmonary hypertension (CTEPH) is potentially curable by surgery. • The triage of patients with pulmonary hypertension currently relies on scintigraphy. • Dual-energy CT (DECT) can provide standard diagnostic information and lung perfusion from a single acquisition. • There is excellent agreement between DECT perfusion and scintigraphy in separating CTEPH and non-CTEPH patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
96
0
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(108 citation statements)
references
References 43 publications
2
96
0
10
Order By: Relevance
“…Thus, it is tempting to speculate that the vascular tree-in-bud pattern in COVID-19 pneumonia may be an important CT marker of immunothrombosis and angiogenesis. The DECT scanning technique, although lacking a routine role in the imaging of lung disease, has certainly attracted attention as an alternative means of assessing pulmonary perfusion in acute and chronic thromboembolic disease (23)(24)(25). In the specific context of chronic thromboembolic disease, there is high concordance between findings on DECT and traditional ventilation-perfusion imaging (24,25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is tempting to speculate that the vascular tree-in-bud pattern in COVID-19 pneumonia may be an important CT marker of immunothrombosis and angiogenesis. The DECT scanning technique, although lacking a routine role in the imaging of lung disease, has certainly attracted attention as an alternative means of assessing pulmonary perfusion in acute and chronic thromboembolic disease (23)(24)(25). In the specific context of chronic thromboembolic disease, there is high concordance between findings on DECT and traditional ventilation-perfusion imaging (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…The DECT scanning technique, although lacking a routine role in the imaging of lung disease, has certainly attracted attention as an alternative means of assessing pulmonary perfusion in acute and chronic thromboembolic disease ( 23 25 ). In the specific context of chronic thromboembolic disease, there is high concordance between findings on DECT and traditional ventilation-perfusion imaging ( 24 , 25 ). Indeed, patterns of perfusion abnormality appear to differ significantly between chronic thromboembolic disease and patients with pulmonary arterial hypertension ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…[13] Recent studies have shown that the diagnostic value for DECT was consistent with V/Q Scan excellently. [14]…”
Section: Discussionmentioning
confidence: 99%
“…Hence, lung abnormalities appear dark on PBV maps. PBV maps can also be merged with conventional CT images to better analyze the lungs’ form and function [ 75 , 76 ].
Fig.
…”
Section: Ct Pulmonary Angiography For Pre-procedural Planningmentioning
confidence: 99%